AFM13 in patients with relapsed or refractory classical Hodgkin lymphoma: final results of an open-label, randomized, multicenter phase II trial. Issue 8 (3rd July 2022) - Sasse, Stephanie; Bröckelmann, Paul Jan; Momotow, Jesko; Plütschow, Annette; Hüttmann, Andreas; Basara, Nadezda; Koenecke, Christian; Martin, Sonja; Bentz, Martin; Grosse-Thie, Christina; Thorspecken, Sven; de Wit, Maike; et al.
Abstract: In patients with relapse of classical Hodgkin lymphoma (cHL) after autologous stem cell transplant, brentuximab vedotin and anti-PD1 treatment, the outcome is poor. To assess the efficacy of the bispecific anti-CD30/CD16A, NK-cell engaging antibody AFM13 and to select the optimal treatment schedule (arm A–C), we initiated a randomized two-stage phase II trial (NCT02321592). Due to slow recruitment, the trial was terminated after treatment of 25 patients. Treatment with AFM13 was well tolerated: only two treatment-associated serious adverse events (SAEs) were reported; all SAEs resolved completely. With an objective response rate (ORR) of 16.7% (1/5 in arm A, 1/11 in arm B, and 2/8 in arm C) and a 12-month progression-free survival (PFS) of 12.6% (95% CI 3.2–28.9), treatment efficacy of AFM13 monotherapy in all evaluable patients was modest. The continuous application schedule (arm C) might be more effective, but the visit schedule should be better aligned with patients' daily life.